Scientific publishing and global university rankings. How well are top publishing universities recognized? - Osmo Kivinen; Juha Hedman; Kalle Artukka (SPRINGER, 2022)
The paper asks to what extent the top 200 universities in scientific publishing in four research fields are the same universities that occupy the top 200 positions in global university rankings. In this article, the top 200 lists of universities in scientific publishing are compiled of universities' contribution rates in four fields: biological, physical, social and life sciences. Out of some 4000 academic institutions included in InCites, the paper identifies 437 top publishing universities in at least one field. The paper analyses the extent to which those universities are covered in six global university rankings' top 200 listings: Academic Ranking of World Universities (ARWU), Performance Ranking of Scientific Papers for World Universities (NTU), QS World University Rankings (QS), Times Higher Education World University rankings (THE), University Ranking by Academic Performance (URAP) and US News and World Report Best Global University Rankings (USNWR). Out of these rankings, URAP, NTU and USNWR are more distinctive than ARWU, QS and THE in covering the 437 top publishing universities in their top 200 listings. Therefore URAP, NTU and USNWR are utilized in analyzing top publishing universities' chances to be recognized. The paper identifies a total of 64 top publishing universities in at least three out of four fields recognized without exception in the top 200 lists of NTU, URAP and USNWR; out of them 24 reside in the USA, 21 in the EU and 19 in the rest of the World. In addition, the paper identifies other (373) top publishing universities variably recognized by the relevant of the three rankings (in terms of odds) depending on the fields in which the universities reach the top 200; odds range from 0.01 (biological sciences) to 12.00 (life, social and biological sciences). The region of residence of these 373 universities also varies, so that those reaching the top 200 in life sciences reside most frequently in the EU, those reaching the top 200 in social sciences in the USA and those reaching the top 200 in physical or in biological sciences in the rest of the World.